2011
DOI: 10.1063/1.3642962
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of β-Ga2O3 single crystals grown by the Czochralski method

Abstract: Electrical properties of nominally undoped β-Ga2O3 crystals grown by the Czochralski method from an iridium crucible under a carbon dioxide containing atmosphere were studied by temperature dependent conductivity and Hall effect measurements as well as deep level transient spectroscopy. All crystals were n-type with net donor concentrations between 6 × 1016 and 8 × 1017 cm−3. The Hall mobility of electrons was on average 130 cm2/Vs at room temperature and attained a maximum of 500 cm2/Vs at 100 K. The donor io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
335
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(387 citation statements)
references
References 30 publications
45
335
3
4
Order By: Relevance
“…Recent ab initio calculations 9 suggest that VO is a deep donor with the (2+|0) level located at The donor in UID β-Ga2O3 was previously suggested to be related to Si based on its presence in the source material with the concentration similar to the free carrier concentration determined from Hall-effect measurements 21 or from the Si-doping studies. 12,13 A recent study also shows that the free carriers activated by annealing in N2 gas are similar to the doped Si concentration.…”
Section: Origin Of the Donormentioning
confidence: 94%
See 2 more Smart Citations
“…Recent ab initio calculations 9 suggest that VO is a deep donor with the (2+|0) level located at The donor in UID β-Ga2O3 was previously suggested to be related to Si based on its presence in the source material with the concentration similar to the free carrier concentration determined from Hall-effect measurements 21 or from the Si-doping studies. 12,13 A recent study also shows that the free carriers activated by annealing in N2 gas are similar to the doped Si concentration.…”
Section: Origin Of the Donormentioning
confidence: 94%
“…19 Hall-effect measurements gave an estimated donor ionization energy in the range of 16-30 meV for conducting β-Ga2O3. 20,21 However, hybrid functional calculations suggested VO to be deep donors and, therefore, cannot be responsible for the n-type conductivity in UID materials. 9 Studies of UID β-Ga2O3 with the conductivity varying in a large range suggested that the Si impurity in the source material (β-Ga2O3 powder) can account for the observed conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Interest is also rising for possible applications as a deep ultraviolet solar blind detector due to its outstanding transparency out to $260 nm. 10,11 However, perhaps the primary driver for the interest is that b-Ga 2 O 3 , with its $4.5-4.9 eV bandgap, 2 is available as a bulk crystal, and therefore, native substrates are available for lattice-matched epitaxial growth of device structures, unlike contemporary wide and ultrawide bandgap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Measured electron mobilities are in the 100-200 cm 2 V −1 s −1 range at room temperature, up to about 500 cm 2 V −1 s −1 in the 100-200 K range for low-doped bulk material, [158,159] and up to even 5000 cm 2 V −1 s −1 at 80 K in high-quality HVPE-grown epitaxial layers. [160] As illustrated in Figure 8, mobility in Ga 2 O 3 appears to be limited by optical phonon scattering at high temperature and ionized impurity scattering at low temperature.…”
Section: Low-field Transportmentioning
confidence: 99%